An Intrinsic Look Into the Industrial Growth in India by Virtue of “FDI” - Pradhan, Prasanna Kumar; Panda, Sitansu (Penerbit Universiti Malaysia Pahang, 2016)
Foreign direct investment (FDI) in India during the era of globalization, high inflation and liberalization have, without any doubt, emerged as one of the most significant source and contributor of external inflow of resources for capital formation. The term FDI is closely associated with structured industrial growth and dynamics of the business environment in India. FDI in the context of industrial growth refers to the bundle of resources that usually flow into a country including capital, production technology, global managerial skills, innovative marketing strategies and access to new markets. In this paper, efforts are made to provide a comprehensive picture of the foreign direct investment ranging from its conception to the factors responsible for making India industrially progressive. A cumulative and an exhaustive study of the overall scenario of FDI in this country will allow having a lucid idea about the utility of the perception, the causes for low flow of FDI and the mechanisms that can be used to make this country attractive enough for foreign investors. It is high time for the government to intensify efforts in the form of reformed legislation to further liberalize the economy so that India can be the most preferred FDI destination in the world to facilitate high rate of Industrialization. This study entirely relies on secondary data collected having concrete references to various websites, textbooks, journals, newspapers, and magazines.